2021
DOI: 10.3390/su13031239
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Some Biodiversity Indicators and Crown Damage of Pinus sylvestris L. in Natural Old Growth Pine Forests

Abstract: Biodiversity at the species and individual levels is one of the fundamental elements characterizing an ecosystem. It is assumed that the greater the level of biodiversity, the more tolerant the environment is to changes in external conditions. In recent years, dynamic climate change has negatively impacted the health of many forest trees across Europe, in particular Scots pine. Tree health is commonly characterized by crown defoliation. The study presented here describes and correlates crown defoliation with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
3
3
0
1
Order By: Relevance
“…The nuclear microsatellite markers used in this study detected medium level of genetic variation in comparison to Scots pine populations from other regions of natural distribution of this species in Europe and Poland. Genetic diversity revealed in our study was very similar to that seen in some populations from Lithuania (Danusevicius et al, 2016), Carpathians (Sofletea et al, 2020) and two stands of Kampinos National Park in Poland (Przybylski et al, 2021). However, in comparison with other Scots pine populations from Poland (Przybylski et al, 2021;Nowakowska, 2016;Lesiczka et al, 2017), Sweden (García Gil et al, 2015, Estonia (Pazouki et al, 2015) it shows a lower level of genetic variation as measured by basic statistics (Table 2).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The nuclear microsatellite markers used in this study detected medium level of genetic variation in comparison to Scots pine populations from other regions of natural distribution of this species in Europe and Poland. Genetic diversity revealed in our study was very similar to that seen in some populations from Lithuania (Danusevicius et al, 2016), Carpathians (Sofletea et al, 2020) and two stands of Kampinos National Park in Poland (Przybylski et al, 2021). However, in comparison with other Scots pine populations from Poland (Przybylski et al, 2021;Nowakowska, 2016;Lesiczka et al, 2017), Sweden (García Gil et al, 2015, Estonia (Pazouki et al, 2015) it shows a lower level of genetic variation as measured by basic statistics (Table 2).…”
Section: Discussionsupporting
confidence: 87%
“…Genetic diversity revealed in our study was very similar to that seen in some populations from Lithuania (Danusevicius et al, 2016), Carpathians (Sofletea et al, 2020) and two stands of Kampinos National Park in Poland (Przybylski et al, 2021). However, in comparison with other Scots pine populations from Poland (Przybylski et al, 2021;Nowakowska, 2016;Lesiczka et al, 2017), Sweden (García Gil et al, 2015, Estonia (Pazouki et al, 2015) it shows a lower level of genetic variation as measured by basic statistics (Table 2). On the other hand, genetic diversity estimates were higher compared to that found in the Finnish and Polish populations studied by Hebda et al (2017) and Wójkiewicz et al (2016) which presented lower values of mean number of alleles, effective number of alleles, observed and expected heterozygosity (Table 2).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it can be assumed that while the genetic variability of the ancient forests of KNP has been influenced by humans, their regeneration processes are spontaneous. The presented results can be interpreted in the context of adaptation of pine trees to different growth conditions, which follows the results of earlier studies by Przybylski et al [6]. The results of the presented studies, based on Krzanowska et al [7] and others, suggest that stands with a high degree of genetic differentiation have a much higher chance of survival and can consequently pass on favourable gene combinations to their offspring.…”
Section: Introductionsupporting
confidence: 88%
“…This indicated that the DY population had relatively high phenotypic diversity and variation. Genetic diversity is the basis of the evolutionary potential of a species to adapt to changes in its external environment [20]. S. cathayensis is a natural hybrid between the genera Populus and Salix with a complex genetic background and high heterozygosity [21,22].…”
Section: Discussionmentioning
confidence: 99%